2018
DOI: 10.1371/journal.pone.0207450
|View full text |Cite
|
Sign up to set email alerts
|

The impact of computerised physician order entry and clinical decision support on pharmacist-physician communication in the hospital setting: A qualitative study

Abstract: BackgroundThe implementation of Computerised Physician Order Entry (CPOE) and Clinical Decision Support (CDS) has been found to have some unintended consequences. The aim of this study is to explore pharmacists and physicians perceptions of their interprofessional communication in the context of the technology and whether electronic messaging and CDS has an impact on this.MethodThis qualitative study was conducted in two acute hospitals: the University Hospitals Birmingham NHS Foundation Trust (UHBFT) and Guy’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
1
16
0
1
Order By: Relevance
“…Some unintended consequences of the implementation of CDSSs have been described, for example, increased pharmacist–physician communication load [ 53 ]. Research has also shown the need for improvement of many aspects of CDSSs such as usability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some unintended consequences of the implementation of CDSSs have been described, for example, increased pharmacist–physician communication load [ 53 ]. Research has also shown the need for improvement of many aspects of CDSSs such as usability [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…For each order, sites were asked to state whether or not the order could be placed or if it was not applicable, for example when the order related to a drug that was prescribed on paper at their site. In addition sites were asked to record the levels of CDS provided for each order using one of five descriptors in Table 1 20. No specific instructions were provided as to how to simulate the orders.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 25 studies, seven were from the UK [1016], four from the US [17–20], four from the Netherlands [2124], three from France [2527], two from Australia [28, 29], two from Saudi Arabia [30, 31] and one each from Denmark [32], Spain [33] and Iran [34]. Nineteen studied commercial systems, one a home-grown system [25], one both a commercial and a home grown [15] system and for four studies it was not possible to establish the system type [11, 30, 31, 34]. Nineteen studies referred to their electronic systems as CPOE, and among these, three specified that the system was for prescribing medication only [2224].…”
Section: Resultsmentioning
confidence: 99%
“…Twelve papers highlighted the impact of eP systems on HCPs’ communication among professions. Two reported a positive impact on HCPs [17, 20], two reported no significant difference [27, 29], three reported a negative impact [22, 23, 26] and five reported a preference for verbal communication over electronic [11, 15, 21, 25, 31]. Two specifically reported a positive impact on doctor-nurse communication since introduction of eP [17, 20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation